THE IMPACT OF MALAYSIA AIRLINES’ ONLINE PAYMENT SYSTEM ON PURCHASE INTENTION AMONG MALAYSIAN CONSUMERS - Mohd Azmi, Mohamad Alif Azmiezal; Ng , Vi Anne; Abu Bazar, Megat Muzammir Megat (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
With the rapid advancement of digital transactions in the aviation industry, the online payment system has become a pivotal element influencing customer purchase intention. This study examines the impact of Malaysia Airlines' online payment system on the purchase intention of Malaysian consumers. The study investigates key factors such as performance expectancy, effort expectancy, and price value, which contribute to consumers’ purchase intentions when using the airline's online payment system. A quantitative research approach was adopted, with data collected through surveys distributed among Malaysian consumers who have utilized Malaysia Airlines' online payment system. Statistical methods including descriptive analysis, reliability testing, correlation analysis, and regression analysis were applied to examine the relationships between variables. The findings reveal that a user-friendly interface, simplified processes, and transparent pricing policies significantly influence consumer trust and satisfaction, thereby shaping their purchase intention. These results provide strategic insights for Malaysia Airlines in refining its online payment system to align with customer preferences, ultimately enhancing customer experience and increasing purchase intention.